2014
DOI: 10.1016/j.curtheres.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration Route on the Pharmacokinetics of Cobalamin in Elderly Patients: A Randomized Controlled Trial

Abstract: BackgroundThe gold standard for cobalamin deficiency treatment is administration of cobalamin by intramuscular injection. The injection is painful and inconvenient, particularly for elderly persons. Cobalamin might also be administered intranasally. Previous studies do not provide insight into the pharmacokinetics of intranasal cobalamin administration in comparison with cobalamin injection.AimTo quantify the pharmacokinetics of intranasally and intramuscularly administered cobalamin to determine if intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(14 reference statements)
1
8
1
Order By: Relevance
“…This study represents a proof of concept for the feasibility of using rapidly dissolving MN arrays for transdermal delivery of vitamin B12. Predicting pharmacokinetics in humans on the basis of animal studies requires further investigation, especially as pharmacokinetic results for elderly people presented by Tillemans et al (2014) demonstrated considerable differences compared to results obtained in the present study. Nevertheless, the patch size necessary to deliver therapeutically relevant amounts of vitamin B12 can be cautiously extrapolated from the data presented here.…”
Section: Discussioncontrasting
confidence: 62%
“…This study represents a proof of concept for the feasibility of using rapidly dissolving MN arrays for transdermal delivery of vitamin B12. Predicting pharmacokinetics in humans on the basis of animal studies requires further investigation, especially as pharmacokinetic results for elderly people presented by Tillemans et al (2014) demonstrated considerable differences compared to results obtained in the present study. Nevertheless, the patch size necessary to deliver therapeutically relevant amounts of vitamin B12 can be cautiously extrapolated from the data presented here.…”
Section: Discussioncontrasting
confidence: 62%
“…To overcome these issues and concerns, recently, intranasal and sublingual VitB12 administrations are being developed and are emerging as being very effective due to their stressless nature. The comparison between intranasal and intramuscular prescription lacks big studies and the available data suggest that intranasal administration has a low bioavailability (between 2% and 5%) which is an appropriate quantity to fulfil the deficiency [ 60 , 61 ]. We must add that in Tillemans’s study, they used hydroxocobalamin solution for injection and cyanocobalamine for spray; these VitB12 forms persist differently in the body and can underestimate the intranasal administration [ 50 , 61 ].…”
Section: Current Medical Practicesmentioning
confidence: 99%
“…route (more rarely intravenous) have also been developed in the setting of B12 deficiency, as the nasal route [ 35 ]. This route of administration of B12 has seen a revival of interest in recent years [ 36 , 37 , 38 , 39 ]. This renewed interest is mainly due to the development of several commercial forms of intra-nasal spray-dried powders or nasal gel of cyanocobalamin.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…To our knowledge, only one recent study (quiet of poor methodological quality) has documented the clinical utility of the nasal vitamin B12 replacement, with regards to pharmacokinetics, efficacy, and safety [ 39 ]. In this study, the estimated cobalamin bioavailability after intranasal administration was 2%.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%